2020
DOI: 10.1371/journal.ppat.1009129
|View full text |Cite
|
Sign up to set email alerts
|

Host restriction of emerging high-pathogenic bunyaviruses via MOV10 by targeting viral nucleoprotein and blocking ribonucleoprotein assembly

Abstract: Bunyavirus ribonucleoprotein (RNP) that is assembled by polymerized nucleoproteins (N) coating a viral RNA and associating with a viral polymerase can be both the RNA synthesis machinery and the structural core of virions. Bunyaviral N and RNP thus could be assailable targets for host antiviral defense; however, it remains unclear which and how host factors target N/RNP to restrict bunyaviral infection. By mass spectrometry and protein-interaction analyses, we here show that host protein MOV10 targets the N pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 65 publications
(130 reference statements)
4
43
0
Order By: Relevance
“…Overexpression of MOV10 also inhibits replication and reduces infectivity of a wide range of exogenous retroviruses, including human immunodeficiency virus type-1 (HIV-1) [35,[42][43][44][45]. Furthermore, MOV10 is an interferon-stimulated gene [46,47], which exhibits broad antiviral activity [46,[48][49][50][51][52][53][54][55]. Apart from retrotransposon restricting and antiviral activities, MOV10 has an essential role in post-transcriptional gene regulation, especially in the microRNA (miRNA) pathway [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of MOV10 also inhibits replication and reduces infectivity of a wide range of exogenous retroviruses, including human immunodeficiency virus type-1 (HIV-1) [35,[42][43][44][45]. Furthermore, MOV10 is an interferon-stimulated gene [46,47], which exhibits broad antiviral activity [46,[48][49][50][51][52][53][54][55]. Apart from retrotransposon restricting and antiviral activities, MOV10 has an essential role in post-transcriptional gene regulation, especially in the microRNA (miRNA) pathway [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Both proviral and antiviral functions have been reported for MOV10. It is required for hepatitis delta virus (HDV) replication but not for the translation of its mRNA ( 37 ), facilitates enterovirus replication ( 38 ), inhibits replication of HIV-1 and other retroviruses at multiple steps ( 39 ), inhibits nuclear import of influenza virus nucleoprotein ( 40 ), inhibits porcine reproductive and respiratory syndrome virus (PRRSV) replication by avoiding nucleocapsid protein trafficking to the nucleus ( 41 ), inhibits hepatitis C virus (HCV) and dengue virus replication by partly unknown mechanisms ( 42 , 43 ), and inhibits bunyavirus replication by blocking several nucleoprotein functions ( 44 ). In the case of hepatitis B virus (HBV), contradictory data have been reported for both its proviral ( 45 ) and antiviral ( 46 ) activities.…”
Section: Introductionmentioning
confidence: 99%
“…The role of MOV10 during bunyaviral infections was only recently studied [ 101 ]. It was shown that SFTSV infection specifically upregulates MOV10 expression in vitro and that MOV10 inhibits the replication of SFTSV and other related viruses (Heartland virus (HRTV) and Guertu virus (GTV)) in infected cells.…”
Section: Inhibition Of Bunyavirus By Ifn-stimulated Genes and Other Antiviral Factorsmentioning
confidence: 99%